Birdlime in Western Myanmar: Preparation, Use, and Conservation Implications for an Endemic Bird - Platt, Steven G.; Platt, Kalyar; Naing, Thet Zaw; Meng, Hong; Ko, Win Ko; Lin, Naing; Tizzard, Robert J.; Myo, Khin Myo; Soe, Me Me; Rainwater, Thomas R. (Ethnobiology Letters, 2012)
Birdlimes are adhesive entangling compounds that passively capture birds by binding them to a substrate and rendering flight feathers useless. We investigated birdlime use among indigenous Chin hunters during a wildlife survey of Natma Taung National Park (NTNP) in western Myanmar (May-June 2011). We found that birdlime is prepared from the sap of various banyan trees (Ficus spp.) collected during the annual dry season (December-May). Birdlime is prepared by boiling sap to remove water, and the finished product is a readily malleable and extremely adhesive compound known locally as nghet phan te kaw (“bird glue”). Hunters employ four principal strategies when using birdlime: 1) limed sticks are placed at waterholes and springs; 2) limed sticks are placed in fruiting trees or nocturnal roost sites; 3) limed sticks are positioned at prominent vantage points and hunters mimic vocalizations to attract birds; 4) small insects (possibly termites) are affixed to a limed pole and serve as bait to attract birds. Large numbers (>200) of birds can reportedly be captured during a single day by hunters using birdlime. At least 186 (63.9%) of 291 species of birds occurring in Natma Taung National Park are thought to be vulnerable to this non-selective hunting strategy. The endangered white-browed nuthatch (Sitta victoriae Rippon Sittidae), a poorly-studied endemic species restricted to high elevation Oak-Rhododendron forest in NTNP, is vulnerable to birdliming, although the impact of hunting on populations remains unclear. We recommend that future investigations determine the sustainability of the Chin bird harvest by relating hunter off-take to recruitment and survivorship of nuthatches. If conservation action is deemed prudent, management plans should be developed in close collaboration with local Chin communities.